NILAI-NILAI KARAKTER DALAM TRADISI LIWETAN SATRI DI KEDIRI - Saidah, Karimatus; Fahmi Imron, Ilmawati; Putri, Kharisma Eka; mumpuni, Atikah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
Liwetan is a tradition to cook and eat from a tray or banana leaves together. This Liwetan is done with some students eating on banana leaves filled with food and side dishes. This tradition is closely related to positive habituation and character values. This article aims to explore the nyantri and liwetan traditions carried out by santri. The research method used is a qualitative method. The results of this study indicate that the nyantri tradition has been carried out from generation to generation as part of the principle of the Kediri community that religious knowledge is more important to learn, the liwetan tradition developed from the beginning to be frugal to become a tradition used to build the character of students who have an attitude, simplicity, togetherness, mutual respect, cooperation, friendship, nationalism and eliminating the boundaries of social stratification.